Controle de constitucionalidade e o ativismo judicial - Martignago, Gisella (2009)
The Constitution of 1988 brought a series of changes in the field of the competence of the Supreme Court, creating new constitutional guarantees such as the warrant of injunction and the direct action of unconstitutionality by omission, extending the list of persons who has the right to bring direct action of unconstitutionality, among others. With the changing composition of Ministers in 2002 and the Constitutional Amendment No. 45, in 2004, a more activist attitude became clear from the part of the Members of the Supreme Court. Another point made in the study is a topic that has aroused great interest in national political-institutional, called judicialization of policy. In this context, the hypothesis under examination demonstrates that the Supreme Court, in an activist attitude, is redefining the limits of their competence. Several issues are raised when the Supreme Court exercises its role as guardian of the Constitution, so as to show its activist attitude